PENGARUH MUTU PELAYANAN TERHADAP PEMANFAATAN INSTALASI FARMASI RSUD AJJAPPANNGE KABUPATEN SOPPENG - Nirwati Nirwati; Hasmin Hasmin; Trimaya Cahya Mulat (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2015)
This study aims to analyze the effect of service quality in a whether partially or simultaneously way to the utilization of pharmacy hospital installation Ajjappannge Soppeng. This study was conducted at Hospital Ajjappannge Soppeng for two months starting from December 2014 to Januari 2015. The method used was quantitative method using a questionnaire by taking 100 patients and family as samples, making the data as respondents were determined by accidental sampling technique, the data were analyzed by using the validity, reliability, and using product moment correlation was continued using multiple linier regression through the test statistics, t test, and test the model provisions. The results of this study showed that the quality of services that include tangible, reliability, responsiveness, assurance, and empathy positive and significant effect whether partially or simultaneously way on the utilization of pharmacy hospital installation Ajjappannge Soppeng.